The Application Of The Alun Concept In The Product Of Wall Hanging Room Decorations Using Macrame Techniques - Nyoman Ayu Permata Dewi; I Nyoman Adi Tiaga (LPPM Institut Desain dan Bisnis Bali, 2023)
Designing wall hanging using the macramé technique is made for room decoration. The design of the shape design is based on the application of the work concept, namely a square. Alun, which means water waves is the main concept in the creation of this work, so colors that match the concept and macramé knots that represent the shape of water waves are used. The creation of this work uses the three pillar work creation method from Sp. Gustami. There are three stages of creating works, namely the exploration stage, the experimental stage, and the embodiment stage. This work also considers four aspects, namely aesthetic aspects, material aspects, functional aspects and technical aspects. Based on this, a wall hanging product was created using the macramé technique measuring 112 cm wide and 110cm high which was used to decorate the room.